Runoff Change in Upper Watershed of Tangwang River Based on CMIP-6 Climate Model - ZHAO Yusu; SUN Yingna; HUANG Xihao (Renmin Zhujiang)
To clarify the future change in air temperature, precipitation, and runoff in the upper watershed of Tangwang River, data from three scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) in the CanESM5 model of coupled model intercomparison project phase 6 (CMIP6) were adopted, and the future air temperature and precipitation were processed based on Delta downscaling method. In addition, future runoff change was estimated according to the soil and water assessment tool (SWAT) hydrological model. The maximum and minimum air temperatures and precipitation will increase in the future (2015–2100), but the growth rate varies in different situations, involving 0.65 °C/10a, 0.65 °C/10a,12.23 mm/10a (SSP1-2.6), 0.25 °C/10a, 0.39 °C/10a, 11.14 mm/10a (SSP2-4.5), and 0.81 °C/10a,0.86 °C/10a, 23.57 mm/10a (SSP5-8.5). Future runoff in the upper watershed of Tangwang River will increase in three scenarios, and the rate of increase is from -2.12% to 52.04%. The peak runoff in August and September in the near term (2017–2050) under SSP1-2.6 and SSP 5-8.5 scenarios and in the middle term (2050–2100) under SSP1-2.6, SSP2-4.5, and SSP5-8.5 scenarios is higher than that in the base period, and the maximum increase is in 36.69 m3/s. In the future, the whole upper watershed of Tangwang River may have a warm and wet phenomenon, and the risk of extreme hydrological events may rise. Simulating the future climate and analyzing the runoff change characteristics of the upper watershed of Tangwang River can provide a scientific basis and theoretical support for regional water resource allocation, water resource utilization, and drought and flood disaster prevention.